Molecular approaches in cassava breeding - Becerra López Lavelle, Luis Augusto (Burleigh Dodds Science Publishing Limited, 2017)
In cassava, as for other major crops, molecular markers can reveal the genetic basis for both qualitative and quantitative phenotypic changes. This chapter examines the genetic diversity of cassava, the process of marker-assisted selection (MAS) and the application of genome sequencing to cassava. The chapter looks ahead to the future potential of genetic engineering of cassava.